Faktor Kesuksesan Pengusaha UMKM Wanita Muslim Pengguna Kanal Digital - Fenty Fauziah; Azhar Latief (Al-Tijary, 2021)
The surefire way to achieve prosperity is entrepreneurship. In the digital era, there are almost no obstacles to starting a business. The only capital is creativity and courage. Anyone can open an online store, without having to open a physical store first, including women. Women business actors are identical to Micro, Small, and Medium Enterprises (MSMEs). Indonesia and Malaysia are countries that have a majority Muslim population. For a Muslim woman, success can be seen when she manages to build a sakinah family. Women's digital entrepreneurship offers flexibility between work and household matters. This study aims to analyze the important factors that help explain the success of Muslim women MSME entrepreneurs who use digital channels in marketing their products. The study was applied through a descriptive-qualitative approach, where the data were primary-based. The objectivity was applied to 103 informants obtained from several MSME communities randomly from Indonesia and Malaysia. We find that social capital is a relevant factor for entrepreneurial success among Muslim women MSME entrepreneurs, the form of social capital is the number of children. This finding supports the idea that Muslim women entrepreneurs who have fewer children tend to spend more time on their business than Muslim women entrepreneurs who have more children. Financial capital projected by income growth also affects success, although income growth is on a small scale. Self-efficacy due to internal factors originating from within MSME female entrepreneurs such as self-confidence and tenacity, they are successful in their business. Religiosity has a significant effect on the success of a Muslim woman entrepreneur.